Publications on ethics in the research process in indexed Peruvian biomedical journals - Carcausto-Calla, Wilfredo Humberto (2017)
Introduction: Worldwide production of ethics in the research process begins to gain prominence; the status of documents published in Peruvian biomedical journals is not known. Objectives: To describe the state of the art on ethics in the research process in indexed Peruvian biomedical journals. Design: Crosssectional descriptive study. Material: Publications on ethics in the research process in indexed Peruvian biomedical journals published in the period 2005-2015, and included in LILACS and SciELO Peru databases. Interventions: Observation and analysis of published documents. Main outcome measures: Frequency and percentages. Results: Of 49 publications between 2005 and 2015, 20.4% (n = 10) appeared in 2008, 12.2% (n = 6) in 2010 and 2011. Regarding the published documents, 24.5% (n = 12) was represented by the editorial section, 22.4% (n = 11) by letters to the editor and original articles. Applied ethics- bioethics was the most approached topic, in 36.7% (n = 18) of the papers, followed by scientific misconduct with 34.7% (n = 17). Less studied subjects were learning-ethics training and ethics committee with 14.3% (n = 7) each. Of the 10 Peruvian indexed biomedical journals indexed, the highest production was found in the Peruvian Journal of Experimental Medicine and Public Health, with 38.8% (n = 19), followed by the Annals of the Faculty of Medicine, with 20.4% (N = 10). Conclusions: The publication on ethics in the research process was low. The most published documents were the editorial section, letters to the editor and original articles. The most studied subjects were applied ethics-bioethics and scientific misconduct.